(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to identify the opportunities and challenges facing the accounting and auditing professions when applying the economic unit of Blockchain technology, which is one of the emerging technologies with high transparency in the presentation of data and information, as it has a decentralized structure capable of achieving integration in the data stored in it, as well as its ability to quickly accomplish sending and receiving data in a short time, the blockchain has made a huge change in the traditional transactions via the Internet by eliminating intermediaries or verifying the authorities, and in order to achieve the goal of the research and test its hypotheses, and due to the changes caused by this technology, a questionnaire form was designed addressed to a number of auditors in Baghdad and the provinces, who would provide information that benefits the objectives of the research, as it was relied on a set of statistical methods to analyze the questionnaire form represented by frequencies, the percentage of the description of the research sample, the arithmetic mean, and the standard deviation, the research has reached a set of results, including that the application of trust chains contributes to the reduction of personal judgments and accounting estimates, in addition to that it works to reduce audit risks in terms of obtaining audit evidence and improve its efficiency and effectiveness, and it also helps in obtaining immediate reports and contributes to achieving transparency through the possibility of tracking the progress of transactions unlike traditional accounting systems